Same-Sex Marriage from the Perspective of Theology and Marriage Law - Baharini, Ely (Notary Journal, 2025)
Same-sex marriage in Indonesia is still considered unacceptable by the wider community because it is considered contrary to national law, norms of decency, values of decency in social life, and religious teachings adopted by the majority of Indonesian people. In the view of Christian theology, the nature of marriage is not only a social institution, but also a picture of the sacred relationship between Christ and His church. God created human beings according to divine design as male and female, with the intention of forming a holy communion of life in the bond of marriage, as stated in Genesis 2:18 and 2:24. However, globalization and cultural change have sparked controversy over LGBT issues, including the legality and ethics of same-sex marriage, both in society and in the church. This study aims to examine the validity of same-sex marriage from the perspective of Indonesian positive law and provide a theological response based on the Christian faith. The research method used is a descriptive study with a literature approach, which examines legal sources and theological literature, including the Bible and recent academic references. The results show that same-sex marriage is declared invalid according to Article 1 of the Marriage Law and Article 1320 of the Civil Code. Theologically, the practice is viewed as a sin and an abomination before God as written in Leviticus 18:22 and 20:13. Therefore, same-sex marriage has no basis of legitimacy legally or from the perspective of Christian ethics.